The Performance of Regional Development Banks during Covid-19 Pandemic - Krisetiawati, Ignasia Sukma (Universitas Negeri Semarang, 2021)
This study aims to determine and analyze the performance of BPD during the 2020 Covid-19 pandemic in Indonesia. The variables used are return on assets, operating expenses and operating income, gross non-performing loans, net interest margin, and loan to deposit ratio. The method used in this research is panel data regression analysis using E-Views 9.0 software. The data used is panel data consisting of cross data of 27 Regional Development Banks in Indonesia and time series data from the I-IV quarter of 2020. The results show that during the Covid-19 pandemic in 2020 BOPO has a significant negative effect on ROA, NPL Gross. has no effect on ROA, NIM and LDR has a significant positive effect on ROA. Penelitian ini bertujuan untuk mengetahui dan menganalisis kinerja BPD selama pandemi Covid-19 tahun 2020 di Indonesia. Variabel yang digunakan yaitu return on assets, beban operasional dan pendapatan operasional, non performing loan gross, net interest margin, dan loan to deposit ratio. Metode yang digunakan dalam penelitian adalah analisis regresi data panel menggunakan software E-Views 9.0. Data yang digunakan adalah data panel yang terdiri dari data silang sebanyak 27 Bank Pembangunan Daerah di Indonesia dan data runtut waktu dari kuartal I-IV tahun 2020. Hasil penelitian menunjukkan bahwa selama pandemi Covid-19 tahun 2020 BOPO berpengaruh negatif signifikan terhadap ROA, NPL Gross tidak berpengaruh terhadap ROA, NIM dan LDR berpengaruh positif signifikan terhadap ROA.